Using a community of inquiry framework to improve descriptive writing in ESL university students in Pakistan - Tufail, Javeria; A. Kadir, Zaemah; Mahmood, Faizah; Arumugam, Nalini (Universiti Teknologi MARA, 2023)
In Pakistan, English is taught as a second language, although being a mandatory subject in the primary classes, the students lack writing skills. However, English language learners struggle with the basic English language and lack the ability to write descriptively. Indeed, the ESL university students have a deficiency in descriptive writing, and the uni-versity results also show a decline in ESL students' descriptive writing. Therefore, it is important to focus on the writ-ing of ESL university students in Pakistan to improve their descriptive writing. To comprehend how the tools, help in the means of learning descriptive writing in the English language, the investigation was made on the CoI framework. It states that learning happens through the correlation and junction of three linked existences: teaching, social, and cognitive. However, matching these with the CoI framework may be one method for helping students understand ways to enhance descriptive writing. Likewise, this study focused on the ESL undergraduate university students and provid-ed insights on the three presences of the Community of Inquiry (CoI) framework, and the study describes the influenc-ing presences related to the descriptive writing of ESL university students. Subsequently, the quantitative data was gathered through convenience sampling from the 30 undergraduates, eight-semester final year ESL students at Punjab Public University of Pakistan. Thus, the perceptions of the ESL students towards CoI were measured by the survey questionnaire, and the findings of the CoI framework of the three (teaching, social & cognitive) presences showed the highest means of cognitive presence (4.42) among all the three presences of CoI, whereas the teaching presence (4.05) and social presence (4.02). Therefore, the study identifies the effective impacts of ESL students on descriptive writing by using the CoI framework in the context of Pakistan. In conclusion, the research suggested a comprehensive under-standing of the concept of CoI through the utilisation of three presences of CoI framework in descriptive writing.